Celiac and Perigastric Lymph Node Metastasis of Prostate Cancer Diagnosed with Endoscopic Ultrasound-Guided Fine-Needle Aspiration - Tan Attila; Reva Ricketts-Loriaux; David A Sauer; Douglas O Faigel (Canadian Journal of Gastroenterology)
Endoscopic ultrasound has been used to diagnose and stage gastrointestinal and nongastrointestinal tumours. To our knowledge, the present report describes the first case of celiac and perigastric lymph node metastasis of prostate cancer diagnosed with endoscopic ultrasound-guided fine-needle aspiration.